Subchronic Toxicity of the New Iodine Complex in Dogs and Rats - Islamov, Rinat; Kustova, Tatyana; Nersesyan, Armen; Ilin, Alexander (Frontiers in Veterinary Science, 2020)
Complexes of iodine (povidone-iodine and cadexomers) are among the most important antiseptics used in clinical and veterinary medicines. However, high local irritation activity and systemic toxicity limits their oral administration. The purpose of the study was to compare the effect of a new complex of iodine (PA, potentiator of anticancer antibiotics), in which iodine is coordinated by carbohydrates and polypeptides) on the organisms of rats and dogs treated orally with the drug for 30 days. Wistar rats and Beagle dogs served as experimental animal models. Effect of PA on the animal organism was examined through the measurements of hormones level changes, hematological and clinical chemistry parameters alterations, necropsy and histological examination. The established maximum tolerated dose (MTD) of 2000 mg/kg PA led to a decrease in the rate of body weight gain in male and female rats. Changes in hematological and certain biochemical parameters in rats at doses of 1000 and 2000 mg/kg were observed. Histological study of the thyroid gland revealed changes in the shape and size of the follicles along with colloid resorption. Administration of a half of MTD (180 mg/kg) and lower doses did not result in any change in dogs (thyroid-stimulating hormone, triiodothyronine, and thyroxine). The results of our study show that the pathogenetic action of PA takes place along the path of induction of an inflammatory response with the development of thyrotoxicosis, rather than hypothyroidism. The mechanism of induction of an inflammatory response is also confirmed by histological studies of lesions of the thyroid gland and testes in rats. The no-observed-adverse-effect level (NOAEL) of PA is estimated to be 180 mg/kg (or iodine 22.8 mg/kg) in dogs, which is equivalent to 100 mg/kg (or iodine 12.3 mg/kg) in humans.